Pengaruh Pijat Oksitosin Terhadap Pengeluaran Kolostrum Ibu Nifas - Ratih Septiana Arpen; Elwitri Silvia; Dina Ayuning Tyas; Dewi Asmawati; Rika Armalini; Metta Julita (Universitas Pahlawan Tuanku Tambusai, 2026)
Colostrum is the first essential fluid for newborns because it contains antibodies, immunoglobulins, and essential nutrients that function to enhance the infant’s immune system. However, in some postpartum mothers, the release of colostrum is often delayed due to insufficient stimulation of the hormone oxytocin, which plays a key role in the let-down reflex. Oxytocin massage is one of the non-pharmacological methods that can increase oxytocin stimulation and thereby accelerate colostrum release. This study aimed to determine the effect of oxytocin massage on colostrum release among postpartum mothers. This research employed a quasi-experimental design with a pretest–posttest with control group approach. The sample consisted of postpartum mothers who met the inclusion criteria, selected using purposive sampling. The measurement of colostrum release was conducted by observing the time of the first colostrum appearance after the intervention. Data were analyzed using statistical tests such as the t-test or Mann–Whitney, depending on the data distribution. The results showed a significant difference in the time of colostrum release between the group that received oxytocin massage and the control group, with a p-value < 0.05. Postpartum mothers who received oxytocin massage experienced earlier colostrum release compared to those who did not receive the intervention. In conclusion, oxytocin massage has a significant effect on accelerating colostrum release among postpartum mothers. It is recommended that healthcare providers implement oxytocin massage as a complementary intervention to enhance the success of early breastfeeding initiation (EBI) and support adequate breast milk production during the postpartum period.